2017
DOI: 10.1177/2397002217709400
|View full text |Cite
|
Sign up to set email alerts
|

What makes leaders resilient? An exploratory interview study

Abstract: Can the boss take the heat? Is he or she tough enough for the job? Can they take it, endure the pressure, tolerate or stand up to it? Although we know that resilient leaders are essential for a healthy and efficient workforce, the resilience of leaders itself is still largely unexplored. Our study aims to identify distinctive resilience factors in leadership and help close this research gap. We interviewed 27 leaders from various industrial sectors, German regions and leadership positions. In a qualitative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 67 publications
(156 reference statements)
1
54
0
Order By: Relevance
“…Empirical research suggests that certain personality traits are positively linked to resilience (Förster & Duchek, ). For instance, Wei and Taormina () argued that people who worry a lot tend to think more thoroughly about how to overcome obstacles, which might have a positive effect on resilience.…”
Section: Individual Resilience In the Workplacementioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research suggests that certain personality traits are positively linked to resilience (Förster & Duchek, ). For instance, Wei and Taormina () argued that people who worry a lot tend to think more thoroughly about how to overcome obstacles, which might have a positive effect on resilience.…”
Section: Individual Resilience In the Workplacementioning
confidence: 99%
“…A strong link has been found between employees’ social competencies, such as emotional intelligence or empathy, and their resilience (Förster & Duchek, ; Kinman & Grant, ). Referring to the theory of high‐quality connections (Dutton & Heaphy, ), which states that connections at work are vital for employees’ health and well‐being, Stephens, Heaphy, Carmeli, Spreitzer, and Dutton () found that an individual’s emotional carrying capacity, defined as the capacity to constructively express positive and negative emotions within a relationship, was positively related to individual resilience and mediated the effects of relationship closeness on resilience.…”
Section: Individual Resilience In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Third, an individual’s attitude and mindset toward their job and professional development help them become resilient during adversity ( Cameron and Brownie, 2010 ; Stevenson et al, 2011 ). Lastly, the work context (e.g., the presence of social support, feedback, sharing of responsibilities and work tasks ( Cameron and Brownie, 2010 ; Burns et al, 2013 ; Lamb and Cogan, 2016 ; McDonald et al, 2016 ; Förster and Duchek, 2017 ) are related to resilience among employees.…”
Section: Review Findingsmentioning
confidence: 99%
“…Bendell and Little (2015) define Leadership as a behavior to help people to achieve something significant, and the act of leadership involves an assumption about values and change theories. Individual traits, situational factors, and behavioral factors are equally important for a leader (Förster & Duchek, 2017).…”
Section: Introductionmentioning
confidence: 99%